Electron beam cross-linking of EVA/TPU blends. (July 2014) - Shamekhi, M. A.; Khonakdar, H. A.; Jafari, S. H.; Damavandi, S.; Goodarzian, N.; Ghaffari, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Ethylene vinyl acetate (EVA) copolymer and thermoplastic polyurethane (TPU) with different blending ratios were melt mixed in an internal mixer. The blends were then exposed to electron beam (EB) irradiation with different doses of 50, 100, 150, 200 and 250 kGy. FTIR spectroscopy and dynamic mechanical thermal analysis (DMTA) were used to investigate the effect of cross-linking and blending ratio on chemical structure as well as solid state viscoelastic properties of the blends. FTIR spectroscopy showed interchain cross-linking during melt blending and also radiation cross-linking during solid state irradiation. Observation of one damping peak for blends at almost all blending ratios was an indication of miscibility of these blends. The results indicated formation of interchain cross-linking stabilised with exposure to EB irradiation. Mechanical properties of the blends were investigated via stress–strain curves. Modulus showed a monotonic increasing trend with the radiation dose, but tensile strength and elongation at break were initially increased and then decreased with increasing radiation dose. This was attributed to two competing parallel factors of strain induced crystallisation and degree of cross-linking.